IMPLEMENTASI HAM GENERASI PERTAMA DALAM INTERNATIONAL COVENANT ON CIVIL AND POLITICAL RIGHTS (ICCPR) PADA KEHIDUPAN POLITIK MASYARAKAT DESA MARGA, TABANAN PROVINSI BALI - Made Feri; Deli Bunga Saravistha (Bajang Institute, 2023)
The first generation of human rights basically spoke about freedom and political life, in other words, these rights were civil and political rights. In this case, it can be exemplified by the right to life, equality before the law, freedom of opinion, the right to a fair legal process, the right to freedom of religion and the right to vote and be elected in elections. The role of the village apparatus is very important in guaranteeing the implementation of freedom of human rights in society which is reflected in the system of government and protection of the rights of the community in the civil and political fields in accordance with the Law of the Republic of Indonesia Number 12 of 2005 concerning Ratification of the International Covenant On Civil And Political Rights Covenant (International Civil and Political Rights) which is accompanied by a Declaration against Article 1 concerning the ratification of the International Covenant on Civil and Political Rights. The obstacles faced in the fulfillment of civil and political rights in the community can be resolved by using a consensus approach bridged by the Village Consultative Body (BPD) and facilitated by the village apparatus. BPD plays an important role in ensuring the civil and political rights of the people of Marga Dauh Puri Village, Marga District, Tabanan Regency, Bali. Moreover, the UN Human Rights Council has opened up opportunities for complaints for individuals, activists and NGOs. So it is interesting to examine more deeply through two problems, namely regarding the selection mechanism and the absorption of understanding of human rights in the regulation and process of selecting village government apparatus, especially related to civil and political rights in the life of the nation and state of the Marga Village community in particular. With a research method that is somewhat different from human rights research in general, namely Juridical Empirical.